IMPACT OF PARENTAL CONFLICTS AND PARENTAL SUPPORT ON CHILDREN’S LIFE SATISFACTION MEDIATING ROLE OF PSYCHOLOGICAL WELL-BEING - Baneeha Zainab; Fouzia Hassan; Um e lela; Kiran Shehzadi; Mishal Zoha (International Journal of Contemporary Issues in Social Sciences, 2024)
Children’s well-being and social behavior can be severely affected by inter-parental disputes. This study investigates whether parental support has a positive effect on a child’s happiness in life and whether there is a connection between peer problems and rising inter-parental conflict. A child learns from watching his parents interact with one another. Because he/she is influenced by the culture around him/her, he/she may, during his/her life, go through several different transformations on multiple levels, physically, psychologically, socially as well as emotionally. Children’s well-being and social behavior can be severely affected by inter-parental conflict. Psychological well-being mediates this association. To conduct mediation studies, data for 150 children ranging between the ages of 11 and 18 were collected from various schools and colleges. The study shows that parental support raises life happiness while higher inter-parental conflict is highly linked to lower psychological well-being and life satisfaction in children. The findings also imply that psychological well-being mediates the relationship between inter-parental conflict and children's life satisfaction, suggesting that as inter-parental conflict increases, parents become less affectionate and communicate negatively with their children, which lowers their social well-being. This paper contributes by highlighting the critical role of familial relationships in shaping children's psychological development and life satisfaction The research took a multi-pronged strategy, combining a descriptive survey method with co-relational analysis. An in-depth investigation into the matter has been carried out making use of a wide variety of databases covering the years 2012 through 2022.